The Role of Notary in Debt Transfer Agreements In Islamic Banking Practices - Vanessa Shania; Aad Rusyad Nurdin (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study examines the agreement for transferring receivables through cessie in Islamic banking, regulated by five fatwas issued by the National Sharia Council–Indonesian Ulema Council (DSN-MUI), namely Fatwa No. 12/2000 on hawalah, Fatwa No. 31/2002 on debt transfer, Fatwa No. 58/2007 on hawalah bil ujrah, and Fatwas No. 103/2016 and No. 104/2016 concerning subjective novation and subrogation based on Sharia principles. The transfer of receivables through hawalah contracts is considered a solution to non-performing financing in Islamic banks, where the notary plays a crucial role as a trusted third party responsible for ensuring the authenticity of every deed, including hawalah agreements. This research aims to understand the regulatory framework governing debt transfers through hawalah contracts, identify problems arising in practice, and analyze the role of notaries in the process. The study employs a doctrinal descriptive-analytical method, focusing on the interpretation of legal norms found in DSN-MUI fatwas, Article 613 of the Indonesian Civil Code, and other relevant legislation, while also examining potential conflicts of norms between Islamic legal principles and civil law in the implementation of hawalah contracts. The findings reveal that ijab and qabul in hawalah contracts do not necessarily require the debtor’s presence, except in the initial financing agreement. Furthermore, notaries must provide legal counseling and adhere to proper deed-making procedures to minimize the risk of future compensation claims if disputes arise.